Bi-reforma do biogás para a produção de hidrogênio utilizando precursores do tipo perovskita a base de níquel e lantânio suportados em óxidos mistos de cério-zircônia - Santos, Dyovani Bruno Lima dos (2017)
In the present work, the performance of catalysts obtained from supported LaNiO3 perovskite precursors were evaluated for biogas bi-reform process. The catalysts were synthesized using 30% LaNiO3, prepared by the sol-gel method and supported on CexZr1-xO2 (x = 1; 0.75; 0.5), which were prepared by the co-precipitation method. An unsupported LaNiO3 precursor was also prepared as reference. The catalysts were characterized by BET surface area (BET), ex situ and in situ X-ray diffraction (XRD), temperature-programmed reduction (TPR), X-ray absorption near edge structure spectroscopy at the L3 edge of cerium and at the K edge of the nickel (XANES). BET results showed that all samples exhibited low surface areas probably due to the high calcination temperature (800 °C). It was also possible to observe that the surface areas of the supports decreased due to the presence of perovskite. However, XRD technique showed that the formation of the perovskite phase occurred without interference of the addition of the supports during the preparation. According to TPR, DRX in situ and XANES, all the catalysts reduced at temperatures below 700 °C and that the addition of zirconium into cerium lattice improved the reducibility of the supports. Thus, the following order was identified for the reducibility: LaNiO3/Ce0.5Zr0.5O2 > LaNiO3/Ce0.75Zr0.25O2 > LaNiO3/CeO2. In order to evaluate the performance of the catalysts in the bi-reforming of biogas, three steps of catalytic tests were carried out. In the first step, a comparison was made between the catalysts at the reaction temperature of 800 °C and molar ratio of 3CH4:1CO2:2H2O. The results showed that the most promising precursor was LaNiO3/Ce0.75Zr0.25O2, since it presented higher catalytic activity. It was also observed that all supported catalysts showed a decrease in CH4 and CO2 conversions, which may be explained by the oxidation process of the nickel particles due to the dissociation of H2O on the surface of the supports. In the second step, catalytic tests were performed with different water flows, using the LaNiO3/Ce0.75Zr0.25O2 precursor. These catalytic tests revealed that the addition of water to the feed had a negative effect on the conversion of CH4 and CO2. Furthermore, the results showed that the higher amount of water fed, the higher H2/CO ratio obtained by the process. Finally, the third step was a comparative between a simple catalyst, Ni/Al2O3, and LaNiO3/Ce0.75Zr0.25O2 precursor. In these catalytic tests, CH4:CO2:H2O molar ratios were changed between dry reforming (3:2:0) and bi-reforming (3:2:2) conditions. It was possible to observe that these catalysts presented different behaviors. The addition of water positively influenced CH4 conversion for Ni/Al2O3 sample, while for LaNiO3/Ce0.75Zr0.25O2, this effect was negative. A possible explanation for this difference could be that the presence of reducible oxides such as ceria and lanthana could be facilitating water dissociation on the surface, generating hydrogen and oxygen. This oxygen could oxidize the surface of nickel particles, which could explain the lower methane conversions obtained for LaNiO3/Ce0.75Zr0.25O2 in bi-reforming conditions.